Prevalence of oral mucosal lesions among elderly population in Chennai: a survey - Rohini S.; Sherlin Herald J.; Jayaraj Gifrina (EDP Sciences, 2020)
Introduction: The oral mucosa serves as a protective barrier against trauma, pathogens and carcinogenic agents. It can be affected by a wide variety of lesions and conditions, some of which may be harmless or with serious complications. Identification and institution of proper treatment of these lesions are an important part of total oral health care. Knowledge of clinical characteristics of oral mucosal lesions such as morphology, location, and duration helps in proper diagnosis and in identifying the type of oral mucosal lesion. The present study was designed to analyze prevalence of oral mucosal lesions in elderly population. Materials and methods: A descriptive pro forma-based study was conducted among the elderly patients visiting the Saveetha Dental College, Chennai, Tamil Nadu, India. Elderly patients within the age 55-90 years were considered as subjects in this study. The pro forma contained basic details of patients such as name, age, sex, occupation, chief complaint, past medical and dental history, family history and personal habits (oral hygiene habits and oral habits). On intra oral examination the characteristic features of oral mucosal lesions were recorded. Result: Seventy five subjects participated in the study. In 75 subjects, there were 55 males and 20 females. The patients ranged from 55 to 90 years old and were categorised into four age groups: 55-60 years, 60-70 years, 70-80 years and 80-90 years. The most common lesions were oral submucous fibrosis (21.33%), smoker's palate (20%), leukoplakia (14.66%) and tobacco pouch keratosis (10.66%). Conclusion: The prevalence of oral habits related lesions in elderly population are more in Indian population because of more exposure to tobacco products in old age and the prevalence of non oral habits related lesions are because of vitamin, dietary deficiency and stress. Hence, proper support and care of aged individuals will help the dentist in proper diagnosis and treatment planning programs.